Assessment of Food Frequency Questionnaire in Patients with Chronic Kidney Disease 5D - P. Dharani Prasad (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: This prospective cross-sectional study aimed to validate the food frequency questionnaire (FFQ) in dialysis patients at the Department of Nephrology. A total of 257 hemodialysis patients were assessed based on socio-demographic, biochemical, and dietary data. The study found that patients predominantly belonged to the age groups of 50–60 years and above 60 years, with chronic kidney disease (CKD) stage 5D being the most reported condition. The FFQs were designed, validated, and implemented to analyze dietary consumption habits, helping in the formulation of evidence-based dietary recommendations. The findings highlight the significance of structured dietary assessment tools in improving patient outcomes during hemodialysis. Materials and Methods: This study was a hospital-based cross-sectional Observational Study conducted in the Department of Nephrology, Sri Venkateswara Institute of Medical Sciences, south Indian a tertiary care hospital, Tirupati, Andhra Pradesh. This study was approved by the Institutional Research and the Ethics Committee of the hospital. The study assessed the clinical profile, risk factors, diet pattern treatment, and outcomes of patients undergoing dialysis. Purpose of the study: The purpose of this study is to evaluate the reliability and validity of a FFQ as a dietary assessment tool for patients undergoing hemodialysis. By designing and validating a structured FFQ, the study aims to improve dietary assessments and enhance nutritional interventions for individuals with CKD stage 5D. Conclusion: The study successfully validated the FFQs in hemodialysis patients, providing valuable insights into dietary habits that impact treatment outcomes. These findings contribute to the development of evidence-based nutritional strategies aimed at improving the well-being of CKD patients undergoing dialysis.